Emerging professional's view of the landscape: Nursing informatics curriculum, competencies, and career opportunities - Adrienne Lewis; Lorraine Block; Laura Peltonen; Lisiane Pruinelli; Maxim Topaz; Erika Lozada Perezmitre (Netherlands, 2022)
The curriculum associated with nursing informatics (NI) education is not standardized, therefore the perspectives of new and emerging nurse informaticians is important. How these curricula differences affect career opportunities of new nursing informaticians, and in turn influenced current career choices will be explored. Synthesizing opinions with themes extracted from a 2014 international study—Advancing nursi informatics in the next decade: Recommendations from an international survey will be summarized.
Nursing Informatics 2018